2006
DOI: 10.1007/s00417-006-0425-0
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric dimethylarginine is not elevated in exfoliation syndrome but symmetric dimethylarginine is related to exfoliative glaucoma

Abstract: A positive correlation of plasma SDMA in respect to P-Hcy in XFGs and increase of SDMA in mild or intermediate hyperhomocysteinemia may indicate SDMA as a marker of developing XFG in hyperhomocysteinemic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Blomster et al 25 evaluated the plasma levels of ADMA, symmetric dimethylarginine and l -arginine in patients with PEX syndrome. In contrast to our results, the authors did not find a significant difference between those with PEX syndrome and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Blomster et al 25 evaluated the plasma levels of ADMA, symmetric dimethylarginine and l -arginine in patients with PEX syndrome. In contrast to our results, the authors did not find a significant difference between those with PEX syndrome and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that impaired nitric oxide signaling might be responsible for nailfold hemorrhages in POAG. 21 Interestingly, some 51,52 but not all studies 53 show that asymmetric dimethyl arginine, an inhibitor of nitric oxide synthase and contributor to endothelial cell dysfunction, is elevated in the aqueous humor and serum of XFS/XFG patients. One needs also to consider that other mechanisms may be operative in the formation of nailfold hemorrhages in XFS/XFG including a tendency for inherent blood clot formation as demonstrated by rotational thromboelastography.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the association of ADMA levels and glaucoma is somewhat controversial mainly because of the limited number of the previous studies. 13,14,21,22 The earlier study with the largest sample size of 211 patients with advanced glaucoma and 295 participants without glaucoma reported that the serum ADMA levels in advanced glaucoma were significantly higher than that of the control participants. 13 Our findings are consistent with the results of this previous study.…”
Section: Discussionmentioning
confidence: 97%